The Effect of the Implementation of the Supplementary Feeding Consumption Compliance Card on the Compliance Level Among Pregnant Women at the North Ponorogo Health Center - Azkia Izzatun Nadifah; Heru Santoso Wahito Nugroho; Astin Nur Hanifah; Nurlailis Saadah (Health Dynamics, 2024)
Background: Chronic Energy Deficiency (CED) is the cause of non-obstetric medical complications in pregnancy that occurs over a long period of time. The Providing Additional Food (PAF) program for vulnerable pregnant women is a supplementation strategy in overcoming nutritional problems, but the program has not been able to run well, based on observations made and also interviews with officers, it is known that some pregnant women have not been regular in consuming PAF biscuits. Researchers want to know the effect of implementing the PAF consumption compliance card on the level of compliance of CED pregnant women at the North Ponorogo Community Health Center. Methods: This study uses an experimental research method. The research design with a pre-experimental approach is in the form of a one-group pretest-posttest design. The sample was taken using the total population sampling technique. The independent variable in this study was the implementation of the PAF consumption compliance card while the dependent variable was the level of compliance of CED pregnant women consuming PAF. Data collection uses interviews and obedient cards as instruments. Data analysis was carried out by normality test and the result of a p value of > 0.05 could be carried out, then the Paired Sample t-Test could be carried out to find out if there was a difference. Results: The results of the Paired samples t-test showed that there was a difference in the compliance of CED pregnant women before and after being given an obedience card, which can be seen at the value of p = 0.0001473. Conclusions: It can be concluded that compliance cards have proven effective in increasing the compliance of CED pregnant women in consuming PAF. Therefore, it is recommended to implement compliance cards as a reminder and monitor for pregnant women regarding PAF consumption.